Time Varying Causality between Oil Price and Precious Metals : Bootstrap Rolling Windows Granger Causality Approach - Zardoub, Amna (International Journal of Energy Economics and Policy, 2024)
The study of the interaction between oil price and precious metals occupies a research activity and pushes various economists to seek implications both on the economic and political level. It is also important to take into account the evolution of the oil and precious metals markets throughout the period of the COVID-19 pandemic and recently the Ukraine-Russian war. In this paper, we examine the link between the oil price and three types of precious metals namely gold, silver and platinum using the rolling window Granger bootstrap causality method. The study is conducted on the monthly data of oil price and precious metals from the period span from January, 2004 to May, 2022. The empirical results lead to a strong unidirectional causality between oil and platinum and absence of causality between oil and the other two metals.